Neck Ultrasound for the Detection of Cervical Lymphadenopathy in Sarcoidosis: An Alternative to Endobronchial Ultrasound. Issue 3 (July 2019) - Ahmed, Mohammed; Daneshvar, Cyrus; Breen, David
Abstract : Background: Sarcoidosis is diagnosed by demonstration of granulomatous inflammation and exclusion of other potential causes. Lung parenchyma and intrathoracic lymph nodes are currently the commonest sites from which tissue is obtained in clinical practice, but historically scalene lymph node biopsy was the procedure of choice for diagnosing sarcoidosis in many institutions. Aim: We aimed to assess the utility of neck ultrasound (NUS) and cervical lymph node needle sampling among patients with stage 1 and 2 sarcoidosis. In addition, we analyzed the potential predictors of cervical lymphadenopathy in this retrospective cohort study. Methods: Patients with evidence of intrathoracic lymphadenopathy and suspected sarcoidosis referred for an endobronchial ultrasound underwent NUS. Those with enlarged cervical lymph nodes underwent fine-needle aspiration and core needle biopsy when technically feasible. Results: A total of 38 patients were included of which 34 (89.5%) underwent endobronchial ultrasound. Sixteen patients had enlarged lymph nodes on ultrasound and 8 (50%) of these underwent needle sampling. Non-necrotizing granulomas were detected in 6 cases (16.8%, 95% confidence interval, 6.1%–31.3%). Cervical lymphadenopathy was significantly associated with the presence of upper paratracheal lymphadenopathy (P=0.018) and the size of mediastinal lymph nodes on computed tomography (P=0.011). Conclusion: NUS and needle sampling of cervical lymph nodes is a potential modality that can be used for the diagnosis of sarcoidosis in a selected group of patients.